2016
DOI: 10.1519/jsc.0000000000001254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preexercise Creatine Ingestion on Muscle Performance in Healthy Aging Males

Abstract: Preexercise creatine supplementation may have a beneficial effect on aging muscle performance. Using a double-blind, repeated measures, crossover design, healthy males (N = 9, 54.8 ± 4.3 years; 92.9 ± 11.5 kg; 179.2 ± 11.1 cm) were randomized to consume creatine (20 g) and placebo (20 g corn starch maltodextrin), on 2 separate occasions (7 days apart), 3 hours before performing leg press and chest press repetitions to muscle fatigue (3 sets at 70% 1-repetition maximum; 1 minute rest between sets). There was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…The results from the countermovement vertical jump test from this study did not show the same response, likely due to the lack of chronic supplementation or the much lower dosage. However, the dosage of the individual ingredients in the supplement was in line with previous research; the chronic supplementation of creatine, nitrate supplements, and beta-alanine are known to be effective after a certain period of use [9,17,18,20,21].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The results from the countermovement vertical jump test from this study did not show the same response, likely due to the lack of chronic supplementation or the much lower dosage. However, the dosage of the individual ingredients in the supplement was in line with previous research; the chronic supplementation of creatine, nitrate supplements, and beta-alanine are known to be effective after a certain period of use [9,17,18,20,21].…”
Section: Discussionsupporting
confidence: 67%
“…Additionally, parsing the supplement into more of its constituents over additional trials (for example, caffeine with beta-alanine) could further elucidate any potential synergistic effects. Finally, administering the supplement chronically and then providing a washout period with subjects could further show efficacy since a number of ingredients have been shown in the literature to be more effective with chronic supplementation [6,9,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have presented some evidence that creatine treatment, in combination with resistance training, enhances gains in muscle mass and strength following exercise beyond what is attainable with resistance exercise alone (Candow et al, 2019). The benefit of creatine therapy alone without resistance training remains unclear; some have suggested that creatine ingestion improves lean muscle mass in the elderly (Gotshalk et al, 2002), whereas others have observed no benefit in muscle mass or strength with creatine administration (Lobo et al, 2015;Baker et al, 2016;Chami and Candow, 2019). However, in elderly subjects, supplementing resistance training with creatine increased lean muscle mass and strength when compared to placebo (Candow et al, 2014;Devries and Phillips, 2014;Chilibeck et al, 2017).…”
Section: Nutritional Supplementationmentioning
confidence: 99%
“…Baker et al showed that creatine administration of at least 12 to 14 weeks was effective in improving muscle performance in healthy aging men, while a single 20 g creatine dose 3 hours before the muscular exertion did not improve strength. This finding may theoretically be explained by the facts that (1) creatine uptake by the skeletal muscle increases during the first 5 days of supplementation, thus one single dose may not be sufficient to build in the muscle an adequate intracellular amount of creatine; and (2) the effects by creatine in the muscle may be at least partially mediated by the increase in the expression of the above‐listed regulatory factors as well as proliferation and differentiation of muscle satellite cells, all events which require time to occur …”
Section: Creatine Administration In Selected Conditions Of Muscle Dammentioning
confidence: 99%